2022
DOI: 10.1111/nph.18496
|View full text |Cite
|
Sign up to set email alerts
|

Plant genome size modulates grassland community responses to multi‐nutrient additions

Abstract: Grassland ecosystems cover c. 40% of global land area and contain c. 40% of soil organic carbon. Understanding the effects of adding nutrients to grasslands is essential because they provide much of our food, support diverse ecosystem services and harbor rich biodiversity.Using the meadow steppe (grassland) study site of Inner Mongolia, we manipulated seven key nutrients and a cocktail of micronutrients to examine their effects on grassland biomass productivity and diversity.The results, explained in structura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 38 publications
2
14
0
Order By: Relevance
“…Previous studies have found that large‐GS species became more dominant after nutrient addition for 72 (Šmarda et al, 2013) and 160 years (Guignard et al, 2016) at the time of data analysis, supporting the general pattern across the 10 years of our experiment. More importantly, our results were in line with a recent study conducted also at the Inner Mongolia grassland (Peng et al, 2022), in which the interactions between GS and nutrient addition can influence aboveground net primary producion and the effect was apparent after 1 year of nutrient addition. In addition to the nutrient use or demand, GS directly affects minimum cell size and its variation has consequences for leaf gas exchanges and water use efficiency (Beaulieu et al, 2008; Simonin & Roddy, 2018).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Previous studies have found that large‐GS species became more dominant after nutrient addition for 72 (Šmarda et al, 2013) and 160 years (Guignard et al, 2016) at the time of data analysis, supporting the general pattern across the 10 years of our experiment. More importantly, our results were in line with a recent study conducted also at the Inner Mongolia grassland (Peng et al, 2022), in which the interactions between GS and nutrient addition can influence aboveground net primary producion and the effect was apparent after 1 year of nutrient addition. In addition to the nutrient use or demand, GS directly affects minimum cell size and its variation has consequences for leaf gas exchanges and water use efficiency (Beaulieu et al, 2008; Simonin & Roddy, 2018).…”
Section: Discussionsupporting
confidence: 93%
“…Indeed, there is evidence that large-GS species became more dominant under conditions with higher nutrient availability (Guignard et al, 2016;Šmarda et al, 2013). Recently, Peng et al (2022) manipulated nutrient availability in the Inner Mongolia grassland and showed that aboveground net primary productivity increased predominantly from large-GS species with the addition of N, and N plus P. Thus, we expect that environmental filtering would have stronger effects on large-GS species than that on small-GS ones.…”
Section: Introductionmentioning
confidence: 90%
“…The mean annual precipitation and temperature in this area are approximately 360 mm and −2.5°C (1957–2016), respectively (Yang et al, 2019, 2022). The soil is classified as Chernozem with 49.67% sand, 31.57% silt, and 18.76% clay and a pH (0–10 cm) of 6.81 ± 0.09 (Peng et al, 2022), according to the classification by Food and Agricultural Organization (IUSS Working Group WRB, 2015). The soil organic carbon and total nitrogen content, total and available phosphorus concentration in the topsoil (0–10 cm) are 38.27 ± 0.88 g kg −1 , 3.17 ± 0.07 g kg −1 , 401.85 ± 15.50 mg kg −1 , and 5.40 ± 0.25 mg kg −1 , respectively (Peng et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…The soil is classified as Chernozem with 49.67% sand, 31.57% silt, and 18.76% clay and a pH (0–10 cm) of 6.81 ± 0.09 (Peng et al, 2022), according to the classification by Food and Agricultural Organization (IUSS Working Group WRB, 2015). The soil organic carbon and total nitrogen content, total and available phosphorus concentration in the topsoil (0–10 cm) are 38.27 ± 0.88 g kg −1 , 3.17 ± 0.07 g kg −1 , 401.85 ± 15.50 mg kg −1 , and 5.40 ± 0.25 mg kg −1 , respectively (Peng et al, 2022). The growing season in the region extends from June to September, which receives more than 70% of the total annual precipitation.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, nutrient enrichments may release polyploids from genome‐material‐cost constraints and enhance genetic and phenotypic advantages associated with polyploidy (Faizullah et al, 2021), such as being larger and more competitive (Thébault et al, 2011; Yang et al, 2021). In support of these predictions, studies have found that polyploidy and GS are positively correlated with cellular N and/or P content (Jeyasingh and Weider, 2007; Kang et al, 2015) and that environmental scarcities in N and/or P often favor the growth and fitness of diploids or organisms with smaller genomes, whereas N and/or P enrichments often have opposite effects, favoring the growth and fitness of organisms with larger genomes (Hessen et al, 2013; Neiman et al, 2013; Šmarda et al, 2013; Guignard et al, 2016; Bales and Hersch‐Green, 2019; Walczyk and Hersch‐Green, 2019; Anneberg and Segraves, 2020; Peng et al, 2022). However, a lack of ploidy‐level‐ and GS‐dependent growth responses to nutrient amendments has also been observed (Sánchez Vilas and Pannell, 2017; Walczyk and Hersch‐Green, 2022), suggesting additional factors inherent to specific organisms and their environments likely contribute to realized material costs, selective constraints, and responses to nutrient availabilities.…”
mentioning
confidence: 99%